The Influence of Tax Planning on the Value of Manufacturing Companies in the Coal Mining Industry Sector Listed on the Indonesian Stock Exchange for the 2018 - 2022 Period - Kristina, Kristina; Abdillah, Abdillah; Bahri, Syamsul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to determine the effect of tax planning and tax avoidance on the value of mining companies listed on the Indonesia Stock Exchange (BEI) both partially and simultaneously. Tax planning in this research is measured by the Effective Tax Rate (ETR), and profitability is measured by the Net Profit Margin (NPM) as an independent variable. Company value is measured by Book Value Per Share (BVS) as the dependent variable. The population used was 20 mining companies. The sample in this research was selected using descriptive methods and 4 companies were obtained as research objects in the 2018 - 2022 period so that the total sample was 25 samples. This type of research uses an analytical approach. The data analysis technique in this research is quantitative data analysis using SPSS 24 statistical software. The analysis methods used are classical assumptions, multiple linear regression, and hypothesis testing. The results of this research show that the significant value of tax planning is 0.80 > 0.05, so partially the tax planning variable (ETR) has no effect on the value of mining companies (BVS) listed on the Indonesian Stock Exchange.